PENGARUH MANAJEMEN LABA DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA SEKTOR PERBANKAN DI INDONESIA) - Fitrianingsih, Dwi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This study aims to examine the influence of earnings management by Discretionary accrual perspective and financial statement by CAMELS perspective on stock return with audit quality as a moderating variable on banking sector. The population of this research are State-Owned Commercial Bank (BUMN) of Persero, Foreign National Private Bank (BUSN) of Foreign Exchange, Non-Foreign Exchange National Private Bank (BUSN) and Mixed Bank (Private Private Domestic and Foreign Private) which existed in Indonesia from 2011 to 2016. The method of data collection in this research are documentation and observation on the annual report of Banking sector. The data processed by using SPSS program version 20.0 by doing simple multiple linear regression approach. The results of this study The result of this research indicate that earnings management which proxies with Discretionary Accrual have negative effect not significant to stock return, financial performance proxies in CAMELS ratio. The result is CAR, BOPO and LDR have a significant positive effect on stock return. However, BDR and NPM have no significant positive effect on stock return. Audit quality as a moderating variable weakness the negative discretionary accrual effect on stock returns. in other words firms audited by (Big Public Accounting Firm) KAP Big 4 indicates to detect and minimize the existence of earning management when compared to firms audited by KAP Non-Big 4 which then giving affect to stock return.Keywords: Earning management, Discretionary Accrual, CAMELS, financial performance, banking.